Practice patterns in pediatric infectious encephalopathy in four centers in Africa - Bacha, Tigist; Obremskey, Alexandra; Buxton, Jessica; Fink, Ericka L.; von Saint Andre-von Arnim, Amelie; Raees, Madiha (Frontiers in Pediatrics, 2024)
Introduction: Infectious encephalopathy (IE), including meningitis, infectious encephalitis, and cerebral abscess, remains prevalent and carries high mortality and morbidity in children, especially in low and middle income countries (LMIC). This study aims to describe the usual care and outcomes of pediatric IE in four LMIC hospitals in sub-Saharan Africa to support evidence-based care guideline development. Methods: This is a secondary analysis of the Prevalence of Acute Critical Neurological disease in children: A Global Epidemiological Assessment - Developing Countries study, a four-week, prospective, observational study in children (1 week-17 year) with IE presenting to referral hospitals in Ethiopia, Kenya, Rwanda, and Ghana. Data collection included diagnostic testing, interventions, and patient outcomes (e.g., mortality, Pediatric Cerebral and Overall Performance Category Scores (PCPC and POPC)). Results: Seventy-two children with IE were enrolled. Most patients were diagnosed with undifferentiated IE (78%, n=56). Specific etiologies included cerebral malaria (10%, n=7), viral encephalitis (4%, n=3), tuberculosis (4%, n=3), bacterial meningitis (3%, n=2), and cerebral abscess (1%, n=1). Fourteen patients (20%) had a head computed tomography performed. Thirty two (44%) children had a lumbar puncture but only 9 samples (28%) were sent for culture. Median time from diagnosis to antimicrobial therapy was 3 hours (IQR 1-12 hours). Half (51%, n=33) of inpatients received intracranial pressure (ICP)-directed treatment but none underwent ICP monitoring. Mortality was 13% (n=9). The percentage of children with a favorable cognitive score decreased from 95% (n=62) prior to admission to 80% (n=52) and 77% (n=50) at discharge for PCPC and POPC respectively. Discussion: IE led to considerable morbidity and mortality in this cohort, and evaluation and management varied across the care continuum. Resource limitations and diagnostic constraints may have affected diagnosis-directed therapy and other aspects of management. Further studies are needed to describe the epidemiology and management of IE in LMICs to inform future treatment protocols, the role of technological and human capacity building to support both basic monitoring and interventions, as well as creative new solutions to emergency and critical care in these settings.